Analysis of the multi-cracking mechanism of brittle thin films on elastic-plastic substrates. (15th December 2019) - Ben Cheikh, I.; Parry, G.; Dalmas, D.; Estevez, R.; Marthelot, J.
Abstract: Thin brittle films on compliant substrates are used in many applications, as soft electronics and solar cells. When submitted to large tensile strains, those systems undergo multi-cracking. A saturation of the cracks pattern is observed, i.e. no new crack is formed above a given nominal applied strain. Moreover, a characteristic distance between the cracks is observed at saturation. A mechanical analysis is carried out in this paper in order to quantitatively predict the saturation phenomenon. Fracture in the brittle layer, delamination at the interface and plasticity in the substrate are taken into account. The results of finite elements simulations show that both the plastic deformation pattern inside the substrate and the strength of the brittle layer are key elements for predicting the cracks pattern at saturation.